PENGGUNAAN MEDIA PEMBELAJARAN ULAR TANGGA RAKSASA DALAM MENINGKATKAN KETERAMPILAN MENULIS PANTUN SISWA KELAS V SDN PASIRJAYA - Meri Sapitri; Riga Zahara Nurani; Hatma Heris Mahendra (STKIP Subang, 2024)
Primary school students' rhyme writing skills are very important in training students' writing skills so that learning must be improved. The aim of this research is to determine the increase in rhyme writing skills by using the snakes and ladders learning media. giant, The research method used in this research is Classroom Action Research (PTK). There was an increase in the creativity of class V students at SDN Pasirjaya in rhyme writing skills. This is shown by an increase in the average student score from 82.10 in cycle I and 90.39 in cycle II, both results are included in the very good category. Apart from that, learning outcomes show an increase from 76.31% learning completeness in cycle I to 86 .84% in cycle II, with 33 out of 38 students achieving learning completion. The conclusion of this research is that the use of giant snakes and ladders learning media is effective in improving the rhyme writing skills of class V students at SDN Pasirjaya.